Effects of suspended and unsuspended additives in short-term aging process of binder - Ali, Tahseen Saad (2014)
Recently, numerous additives have been blended in asphalt binder to enhance the performance of pavement mixture. However, the use of these modified binders can be problematic as their outcomes on site and in road construction are unpredictable. Meanwhile, many stick to using the same known additives because they are tested and the results predictable and do not experiment with new and possibly better alternatives that could yield improved results. The poor correlation of fatigue and rutting potentials of asphalt binder with the asphalt mix is the main concern in this research. Modified asphalt properties are different in specifications according to the additive type and behavior within the modified binder and as a result of this, there is a fear of unpredictable pavement failure. Such a passive attitude will mean ignoring the potential advantages of the asphalt concrete mix in favor of the asphalt binder which faces problems of rutting and fatigue. Accordingly, the additives are classified into two groups: non-suspended and suspended modified binders. Moreover, the suspended additives continue to be used and the inherent problems remain. These two groups have been compared as they are totally different in their physical properties – one melts while the other is suspended within the binder formation. This study evaluates the non-suspended and suspended additives. Each group consists of different types of additives. Group one (melted) is divided into two additives, ethylene vinyl acetate and tire rubber powder. Group two (suspended) consists of hydrated mineral filler and oil palm cellulose fiber. The physical tests penetration and softening point and the superpave test represents rotational viscosity, rolling thin film oven test RTFO for short-term aging and lastly DSR which are used to evaluate the non-suspended and suspended additives. The main tool for group evaluation is conducted by using the dissipated energy approach to diagnose the failure. The stress sweep test is chosen to run the DSR test. The results reveal the superior resistance to the shear resistance that is represented by the non-suspended additives modified binders. The limit state is established for the non-suspended additives especially for the NSEU (2%-8%) and NSEA (4%-8%). Lastly, the non-suspended modified binders reduce the rutting problems more than the suspended additives modified binders.